Implications of Transformational Leadership of School Principals and Work Culture on Teacher Work Motivation at SMP Negeri Sub Rayon 11 Semarang City - Wasminto, Bambang; Kusumaningsih, Widya; Violinda, Qristin (Cetta: Jurnal Ilmu Pendidikan, 2025)
Teachers' work motivation is one of the main challenges in improving the quality of education in Indonesia, especially in SMP Negeri Sub Rayon 11 Semarang City which still records a teacher work motivation rate of only 41.5%. This condition requires intervention from the managerial aspect, especially in terms of the principal's leadership style and the work culture applied in the school. This study aims to analyze the influence of transformational leadership of school principals and work culture on teachers' work motivation at SMP Negeri Sub Rayon 11 Semarang City. This study uses a quantitative approach with a survey method involving 116 ASN teachers. Data was collected through a questionnaire and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with Smart PLS 3.3.3 software. The results showed that transformational leadership had a positive and significant effect on teachers' work motivation (β = 0.301; p = 0.001) and work culture also had a positive and significant effect (β = 0.365; p = 0.000). Simultaneously, these two variables contributed 45.6% to the variation in teachers' work motivation (R² = 0.456). The conclusion of this study is that strengthening a conducive work culture and the implementation of transformational leadership by school principals can effectively increase teachers' work motivation. These findings also provide practical implications for school managers to create an inspiring and collaborative work environment in supporting the optimal performance of teachers in schools. These findings are expected to be a reference for school managers and policy makers in efforts to improve the quality of education at the junior high school level.